Economic Intelligence system and decision making: Proposal of a theoretical model. - Yahya EL MOUNTASSIR (Moroccan Journal of Quantitative and Qualitative Research, 2021)
The quality of decision-making depends on a set of ad hoc information; Economic intelligence recognizableas the use of information for strategic decision making. From this point of view, it can be considered as a process covering two scientific fields; information systems and decision-making. Theorganization is forced to look for the best ones which meet its needs.